Workshop Persiapan Sertifikasi Ahli K3 Umum oleh Politeknik LP3I Jakarta Bekerjasama Dengan Lembaga Competence Development Center (CDC) LP3I Secara Daring - Kaban, Karya Bakti; Rahmadhani, May Vitha; Sirait, Edison P.; Zulfikar, Ali; Permana, Amon Gari (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Certification and appointment as a General K3 Expert is a government program to reduce accidents and illnesses in the world of work, so as to increase work safety, profits and a positive image for the company. Occupational safety and health (K3) has become an important issue, not only on a national scale, but also on an international scale. Every company is required to implement K3 requirements. K3 no longer only belongs to companies in the oil and gas, mining, construction and manufacturing projects, but has spread to all types of companies. The profession in the field of K3 has become a promising profession for the next few decades. However, knowledge in the field of K3 is not mandatory only for employees in the field of K3, but is mandatory for all employees. Minister of Manpower Regulation No. 2 of 1992 has regulated the procedures for appointing General K3 Experts. "Every company that has 100 employees or more, or has high occupational risks, is required to have a P2K3 and at least one General K3 Expert. "K3 experts are technical workers with special skills from outside the Department of Manpower who are appointed by the Minister of Manpower to monitor compliance with the Work Safety Law." General K3 experts are an extension of the government in supervising work in the workplace, so that it complies with statutory requirements set by the government, so as to reduce risks and incidents, whether accidents or work-related illnesses. After passing this certification, individuals will have legally recognized authority to become an K3 Expert in their workplace. To take part in general K3 expert certification, knowledge and skills are required, including practical experience. To know and be skilled, of course training or workshops are needed. This activity aims to provide education and training in the form of online workshops to build skills and provide an understanding of K3 to professional workers as well as preparation for taking General K3 Expert certification either at the National Professional Certification Agency (BNSP) or at the Ministry of Manpower (Kemenaker). The output target of this community service is an article published on electronic media, activity videos and increasing partner empowerment, namely the creation of professional and competent workers in the field of K3 experts in particular.